Clinical features of nursing and healthcare-associated pneumonia due to COVID-19. Issue 7 (July 2022) - Miyashita, Naoyuki; Nakamori, Yasushi; Ogata, Makoto; Fukuda, Naoki; Yamura, Akihisa; Ishiura, Yoshihisa; Nomura, Shosaku
Abstract: Introduction: The objective of this study was to clarify the clinical differences between nursing and healthcare-associated pneumonia (NHCAP) and community-acquired pneumonia (CAP) due to COVID-19. We also investigated the clinical characteristics to determine whether there is a difference between the variant and non-variant strain in patients with NHCAP due to COVID-19. In addition, we analyzed the clinical outcomes in NHCAP patients with mental disorders who were hospitalized in a medical institution for treatment of mental illness. Methods: This study was conducted at five institutions and assessed a total of 836 patients with COVID-19 pneumonia (154 cases were classified as NHCAP and 335 had lineage B.1.1.7.). Results: No differences in patient background, clinical findings, disease severity, or outcomes were observed in patients with NHCAP between the non-B.1.1.7 group and B.1.1.7 group. The median age, frequency of comorbid illness, rates of intensive care unit stay, and mortality rate were significantly higher in patients with NHCAP than in those with CAP. Among the patients with NHCAP, the mortality rate was highest at 37.5% in patients with recent cancer treatment, followed by elderly or disabled patients receiving nursing care (24.3%), residents of care facilities (23.0%), patients receiving dialysis (13.6%), and patients in mental hospitals (9.4%). Conclusions: Our results demonstrated that there were many differences in the clinical characteristics between NHCAP patients and CAP patients due to COVID-19. It is necessary to consider the prevention and treatment content depending on the presence or absence of applicable criteria for NHCAP.